Amelioration of pancreatic fat accumulation in Japanese type 2 diabetes patients treated with sodium‐glucose cotransporter 2 inhibitors: a retrospective study - Tomomi Horii; Junji Kozawa; Shingo Fujita; Yoshiya Hosokawa; Takekazu Kimura; Yukari Fujita; Ayumi Tokunaga; Kenji Fukui; Iichiro Shimomura (Wiley, 2021)
Abstract Background Prior reports have suggested that pancreatic fat is related to type 2 diabetes. Sodium‐glucose co‐transporter‐2 (SGLT‐2) inhibitors are expected to reduce ectopic fat accumulation. Aim This study assessed the effect of SGLT‐2 inhibitors on pancreatic and liver fat accumulations in patients with type 2 diabetes. Materials and Methods Retrospective analyses of indices of pancreatic and liver fat accumulations were conducted in 22 type 2 diabetes outpatients who were receiving SGLT‐2 inhibitors for more than 12 weeks. The differences between the pancreatic (P) or liver (L) and splenic (S) computed tomography values were evaluated. Results Fatty pancreas was defined as P−S < −8 Hounsfield Unit (HU), and the number of patients with fatty pancreas was 11 (50%). Fatty pancreas significantly improved after SGLT‐2 inhibitor use (median, −20.8; IQR, −34.8 to −14.3 HU vs. median, −14.6; IQR, −29.5 to −7.8 HU; p = 0.041). Fatty liver was defined as L−S ≤ 3.9 HU, and the number of patients with fatty liver was 11 (50%). Fatty liver significantly improved after SGLT‐2 inhibitor use (median, −4.3; IQR, −23.0 to 3.0 HU vs. median, −0.7; IQR, −5.2 to 6.3 HU; p = 0.016). Conclusion Pancreatic fat and liver fat accumulations might be reduced after treatment with SGLT‐2 inhibitors in type 2 diabetes patients with intense cumulative fat depositions in these organs.